Synthesis of uniform Ni nanoparticles encapsulated in ZSM–5 for selective hydrodeoxygenation of phenolics. (July 2022) - Li, Sen; Guo, Longhui; He, Xinyu; Qiao, Congzhen; Tian, Yajie
Abstract: Bio–oil as the promising renewable resources to replace fossil fuels, requires upgrading into deoxygenated fuel. Zeolite supported base metal catalysts have been deemed highly efficient for the hydrodeoxygenation (HDO) of bio–oil, but facing a degraded activity due to metal aggregation. In this study, uniform Ni nanoparticles (∼4 wt%) encapsulated in ZSM–5 zeolites (Ni@ZSM–5s) were synthesized by a one–pot method for catalytic HDO of phenolic compounds. The Ni dispersion was found to be significantly enhanced in the Ni@ZSM–5s catalysts after encapsulation compared with a catalyst prepared by wetness impregnation (Ni/ZSM–5), which is ascribed to the strong interaction between the Ni and the zeolite surface. The Ni@ZSM–5s catalysts show higher HDO activities for phenolics than the Ni/ZSM–5 catalyst, owing to the enhanced adsorption and spillover of active hydrogen by the highly dispersed Ni species. Ni@ZSM–5–50 (Si/Al of 50) gave cyclohexane yield of 91.6% at 250 °C, through sequenced hydrogenation and deoxygenation of anisole. Moreover, the Ni@ZSM–5–100 (Si/Al of 100) with decreased acidities further gave an enhanced TOF value for the conversion of phenolics. From the FT–IR spectrum obtained for adsorbed anisole, the reduction of acidities is determined to facilitate the desorption of intermediates, which accelerates the initial hydrogenation.